Effectiveness of the Safety Friendly Program in reducing accident frequency rate - Naim Fathoni; Doni Hikmat Ramdhan (Program Studi Ilmu Keperawatan-fakultas Ilmu Kesehatan Universitas Malahayati, 2026)
Background: Occupational accidents remain a major challenge in the mining industry because mining operations involve complex activities and high-risk working conditions. To prevent accidents and improve safety performance, PT X implemented the Safety Friendly Program, which includes safety observations, safety inspections, and management engagement activities. An evaluation of the program is needed to determine whether its implementation is accompanied by an improvement in occupational safety performance. Purpose: To analyze the effectiveness of the Safety Friendly Program in reducing the Accident Frequency Rate (AFR) at PT X. Method: A quantitative approach with a time-series comparative design. Secondary data were obtained from the Health, Safety, and Environment Department of PT X from July 2025 to March 2026. The data included safety observations, safety inspections, management engagement activities, and AFR. Data were analyzed descriptively using IBM SPSS Statistics version 25 and presented in tables and trend analyses to compare changes across the study periods. Results: The Safety Friendly Program was implemented consistently throughout the study period. Safety observations reached 513 activities in the third quarter of 2025, 512 activities in the fourth quarter of 2025, and 494 activities in the first quarter of 2026. Safety inspection findings increased from 279 in the fourth quarter of 2025 to 290 in the first quarter of 2026. The number of workers involved in management engagement activities also increased from 293 in the third quarter of 2025 to 309 in the first quarter of 2026. During the same period, AFR decreased from 10.57 in the third quarter of 2025 to 8.02 in the fourth quarter of 2025 and further declined to 3.07 in the first quarter of 2026. Overall, AFR decreased by 70.96%. Conclusion: The consistent implementation of the Safety Friendly Program was accompanied by a substantial decline in AFR during the study period. Safety observations, safety inspections, and management engagement activities may support accident prevention and strengthen safety practices in mining operations. However, this descriptive trend should not be interpreted as evidence of a causal relationship. Continued implementation and periodic evaluation are recommended to improve occupational safety performance.